Displaced persons, resettlement and the legacies of war : from war zones to new homes - Stroja, Jessica (Routledge studies in modern history, 2022)
"This book provides a case study on the ongoing impact of displacement and encampment of refugees who do not have access to resettlement support services, or are resettled in locations of low cultural and linguistic diversity. Following the journeys of displaced families and children who left Europe after the Second World War to seek resettlement in Queensland, Australia, this book brings together the rarely heard voices of these refugees from written archives, along with material from more than 50 oral history interviews. It thoroughly explores the impacts of displacement, encampment and eventually resettlement in locations without resettlement facilities or support networks. In so doing, the book brings to light important findings that can be used to help understand the experiences of those impacted by contemporary refugee crises, and can be considered when developing responses and assistance in locations where there is a lack of diversity or support for refugees. This book will be of interest to scholars and students studying and researching the history of migration, sociology of migration, psychological effects of migration and displacement, as well as demography. Practitioners and policy makers will also be able to draw from this book when considering the long-term impacts of responses to contemporary refugee crises"--